THE CONTRIBUTION OF LEARNING ANXIETY, TEACHER-STUDENT RELATIONSHIPS, AND SELF-CONCEPT TOWARD THE SPEAKING SKILLS OF THE TENTH GRADE STUDENTS IN SMA N 1 BANGLI - WEDAYANTHI, LUH MADE DWI (Jurnal Pendidikan Bahasa, 2012)
ABSTRACT Wedayanthi, Luh Made Dwi (2012). The Contributions of Learning Anxiety, Teacher-Student Relationships, and Self-Concepts toward the Speaking Skills of the Tenth Grade Students in SMA N 1 Bangli. Thesis, Language Education Study Program, Postgraduate Program, Ganesha University of Education. Â  This thesis has been examined and corrected by: Supervisor I: Dra. Luh Putu Artini, M.A. Ph.D Supervisor II: Dr. Ni Made Ratminingsih, M.A. Â  Keywords: contribution, learning anxiety, teacher-student relationship, studentâs self-concept, speaking skills. Â  This study was a correlational research that aimed to know the contribution of learning anxiety, teacher-student relationships, and studentsâ self-concept toward the tenth grade studentsâ speaking skills. It was conducted in SMA N 1 Bangli. In this study there were 127 students used as the samples from 231 populations. All of them were the tenth grade students. Before the real data collection was done, the tryout of instrument was conducted. After the tabulation of the real data, the pre-requisite tests were done; normality, linearity, multicollinearity, autocorrelation, and heterocedasticity.Â  Simple regression and multiple regressions were conducted after the pre-requisite tests were done.Â  The simple regression was done to determine the predictor contribution to the criterion variable. After the data were calculated by using SPSS, there were four results from the research questions in this study. The first, there is a relationship between learning anxiety and speaking skills and it contributed 34.66% to speaking skills. It means, the higher learning anxiety owned by the students, the higher speaking skills done by the students.Â  The second, there is a relationship between teacher-student relationships and speaking skills, the contribution is 10.59%. From the contribution, it could be concluded that the better level of teacher-student relationships led the student to have higher level of participation. The third, there is a relationship between studentsâ self-concept and speaking skills, it contributed 5.26%. From all of the contribution from each predictor (X1,2,3) to speaking skills (Y), studentsâ self-concept got the lowest level then the other, it means that studentsâ self-concept need to be increased by the students. Based on the determination above, it could be concluded that (1) there was contribution of studentsâ learning anxiety toward speaking skills, (2) there was contribution of teacher-student relationships toward speaking skills, (3) there was contribution of studentsâ self-concept toward speaking skills, and (4) there was a contribution between studentsâ learning anxiety, teacher-student relationships, and studentsâ self-concept toward speaking skills of the tenth grade senior high school in SMA N 1 Bangli in the academic year 2011/2012.Â ABSTRAK Wedayanthi, Luh Made Dwi (2012). Kontribusi Kecemasan dalam Belajar Bahasa, Hubungan Guru dan Siswa, dan Konsep Diri Siswa terhadap Skill Berbicara Siswa Kelas Sepuluh di SMA N 1 Bangli. Tesis Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Pendidikan Ganesha. Â  Thesis ini telah dibaca dan diperbaiki oleh: Pembimbing I: Dra. Luh Putu Artini, M.A. Ph.D Pembimbing II: Dr. Ni Made Ratminingsih, M.A. Â  Kata Kunci: kontribusi, kecemasan dalam belajar, hubungan sguru dan siswa, konsep diri siswa, skill berbicara Studi ini bertujuan untuk mengetahui kontribusi kecemasan belajar, hubungan guru dan siswa, dan konsep diri terhadap skill berbicara siswa kelas sepuluh. Studi ini dilaksanakan di SMA N 1 Bangli. Dalam studi terdapat 127 siswa sampel dari 231 populasi. Sebelum data dikumpulkan, uji pra-syarat dilaksanakan seperti normalitas, linearitas, multikollinear, autokorelasi, dan heterokedasticitas. Regresi sederhana dan regresi berganda dilaksanakan setelah uji prasyarat selesai. Regresi sederhana dilaksanakan untuk mencari hubungan prediktor dan kriteria variabel. Setelah data dihitung menggunakan SPSS, diperoleh hasil penelitian sebagai berikut; pertama, terdapat hubungan antara kecemasan dalam belajar dan skill berbicara, yang berkontribusi sebanyak 34.66. Hal ini berarti, semakin tinggi kecemasan dalam belajar yang dimiliki siswa, semakin tinggi skill berbicara. Kedua, ada hubungan antara guru dan siswa dengan skill berbicara siswa, yang berkontribusi 10.59%. Dari kontribusi tersebut, dapat disimpulkan bahwa semakin baik tingkat hubungan guru dan siswa semakin baik pula skill berbahasa Inggris siswa. Ketiga, ada hubungan antara konsep diri siswa dengan skill berbicara, yang berkontribusi 5.26%. Berdasarkan semua kontribusi dari setiap predictor (X1,2,3) terhadap skill berbicara. Konsep diri siswa mempunyai hubungan yang paling rendah daripada yang lainnya. Hal ini berarti bahwa konsep diri siswa perlu ditingkatkan oleh guru dalam diri siswa itu sendiri. Berdasarkan semua temuan di atas dapat disimpulkan bahwa; (1) terdapat kontribusi antara kecemasan dalam belajar bahasa terhadap skill berbicara, (2) terdapat kontribusi antara hubungan guru dan siswa terhadap skill berbicara siswa, (3) terdapat kontribusi antara konsep diri siswa terhadpa skill berbicara, dan (4) terdapat kontribusi antara kecemasan belajar siswa, hubungan guru dan siswa, dan konsep diri siswa terhadap skill berbicara pada kelas sepuluh di SMA N 1 Bangli pada tahun ajaran 2011/2012.